2012
DOI: 10.1007/s10534-012-9586-y
|View full text |Cite
|
Sign up to set email alerts
|

Human apo-lactoferrin as a physiological mimetic of hypoxia stabilizes hypoxia-inducible factor-1 alpha

Abstract: Apo-form of human lactoferrin (LF) is a potent iron chelator, this feature being similar to the iron-binding properties of a synthetic chelator desferoxamine (DFO). The latter stabilizes the principal adaptive transcriptional hypoxia-inducible factor-1 alpha (HIF-1α). Since DFO is known as a pharmacological mimetic of hypoxia it was decided to test whether apo-LF is able to perform as such. Mice either injected intraperitoneally or given per os apo-LF displayed HIF-1α in liver, lungs, heart, brain, spleen and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 95 publications
0
23
0
Order By: Relevance
“…How synaptic activity regulates α-secretase remains unclear, although studies implicate HIF-1α as a mediator governing ADAM10 activation (Barsoum et al, 2012). Recently, (Shukla et al (2015)) observed that ERK phosphorylation upregulated ADAM10 through HIF-1α activation, and Lf is also known as a normoxic mimetic of hypoxia, capable of stabilizing HIF-1α (Zakharova et al, 2012). To determine whether upregulation of the ADAM10 protein by hLf in APP/PS1 mice occurred via the same pathway, we analyzed ERK1/2, HIF-1α, and CREB in the extracts of brain tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…How synaptic activity regulates α-secretase remains unclear, although studies implicate HIF-1α as a mediator governing ADAM10 activation (Barsoum et al, 2012). Recently, (Shukla et al (2015)) observed that ERK phosphorylation upregulated ADAM10 through HIF-1α activation, and Lf is also known as a normoxic mimetic of hypoxia, capable of stabilizing HIF-1α (Zakharova et al, 2012). To determine whether upregulation of the ADAM10 protein by hLf in APP/PS1 mice occurred via the same pathway, we analyzed ERK1/2, HIF-1α, and CREB in the extracts of brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that LfR is involved in Lf-induced activation of the ERK1/2 and CREB, these two pathways might regulate each other and co-regulate downstream functions (Ikoma-Seki et al, 2015). Moreover, it has been reported that hypoxia contributes to ADAM10 transcription via HIF-1α activation (Barsoum et al, 2011), and Lf acts as a normoxic mimetic of hypoxia capable of stabilizing HIF-1α (Zakharova et al, 2012). To further investigate the mechanism underlying Lf-mediated upregulation of ADAM10, mitigation of amyloidosis, and inflammation, we next assessed the expression of HIF-1α and VEGF protein, and the activation of ERK1/2 and CREB in the APP/PS1 mouse brains in both hLf-and vehicletreated mice.…”
Section: Lf Treatment Enhanced Erk1/2 Phosphorylation and Upregulatedmentioning
confidence: 98%
See 1 more Smart Citation
“…Intraperitoneal injections to mice and rats of either human or bovine LF resulted in appearance of heterologous complexes CP-LF that were rapidly eliminated from the bloodstream (Sokolov et al 2014). It was also shown that apo-LF is a physiological mimetic of hypoxia capable of stabilizing HIF-1a and increasing the expression of hypoxia-inducible target genes encoding such proteins as erythropoietin (EPO) and CP (Zakharova et al 2012). Our suggestion was that chelating capacity of apo-LF favors the inhibition of iron-dependent prolyland asparaginyl-hydroxylases (PHD and/or FIH) which normally cause destabilization of HIF-1a.…”
Section: Introductionmentioning
confidence: 87%
“…Ferroxidase activity of ceruloplasmin prevents the ubiquitin-mediated degradation of ferroportin [64]. Participation of LF in iron regulation is also mediated via stabilization of iron-sensitive hypoxia-inducible factors-1 alpha and -2 alpha [65,66]. These transcription factors up-regulate the synthesis of erythropoietin, which demonstrated neuroprotective effects distinct from its antianemic functions [67].…”
Section: Links Between Lactoferrin and Parkinson Diseasementioning
confidence: 99%